Indigenously developed multipurpose acrylic head phantom for verification of IMRT using film and gel dosimetry. (4th March 2013) - Gopishankar, N.; Vivekanandhan, S.; Rath, G.K.; Laviraj, M.A.; Senthilkumaran, S.; Kale, S.S.; Thulkar, S.; Bisht, R.K.; Subramani, V.
Abstract : The purpose of this study was to validate the newly designed acrylic phantom for routine dosimetric purpose in radiotherapy. The phantom can be used to evaluate and compare the calculated dose and measured dose using film and gel dosimetric methods. In this study, a doughnut‐shaped planning target volume ( 8 . 54   cm 3 ) and inner organ at risk ( 0 . 353   cm 3 ) were delineated for an IMRT test plan using the X‐ray CT image of the phantom. The phantom consists of acrylic slabs which are integrated to form a human head with a hole in the middle where several dosimetric inserts can be positioned for measurement. An inverse planning with nine coplanar intensity‐modulated fields was created using Pinnacle TPS. For the film analysis, EBT2 film, flatbed scanner, in‐house developed MATLAB codes and ImageJ software were used. The 3D dose distribution recorded in the MAGAT gel dosimeter was read using a 1.5 T MRI scanner. Scanning parameters were CPMG pulse sequence with 8 equidistant echoes, TR = 5600, echo step = 22 ms, pixel size = 0.5 times 0.5, slice thickness = 2   mm . Using a calibration relationship between absorbed dose and spin‐spin relaxation rate (R2), R2 images were converted to dose images. The dose comparison was accomplished using in‐house MATLAB‐based graphical user interface named "IMRT3DCMP". For gel measurement dose grid from the TPS was extracted and compared with the measured dose grid of the gel. Gamma index analysis of film measurement for the tolerance criteria of 2%/2 mm, 1%/1 mm showed more than 90% voxels pass rate. Gamma index analysis of 3D gel measurement data showed more than 90% voxels pass rate for different tolerance criteria of 2%/2 mm and 1%/1 mm. Overall both 2D and 3D measurement were in close agreement with the Pinnacle TPS calculated dose. The phantom designed is cost‐effective and the results are promising, but further investigation is required to validate the phantom with other 3D conformal techniques for dosimetric purpose. PACS numbers: 87.53.Kn, 87.55.km, 87.56.N‐